Apathy, cognitive function and motor function in Alzheimer's disease - Hernandez, Salma S. Soleman [UNESP]; Vital, Thays Martins [UNESP]; Garuffi, Marcelo [UNESP]; Stein, Angélica Miki [UNESP]; Teixeira, Camila Vieira Ligo [UNESP]; Costa, José Luiz Riani [UNESP]; Stella, Florindo [UNESP] (Associação de Neurologia Cognitiva e do Comportamento, 2012)
The aims of this study were to characterize the presence of apathy in patients with AD, determine the relationship between apathy, motor function and cognitive function, and to verify differences among patients stratified by level of apathy in relation to cognitive and motor abilities.

Os objetivos deste estudo compreendem: caracterizar a presença de apatia em pacientes com doença de Alzheimer (DA); verificar se há relação entre apatia, funções cognitivas e funcionalidade motora dos mesmos e analisar se há diferenças entre os pacientes, separados por nível de apatia, em relação às suas funções cognitivas e funcionalidade motora.
Apatia, funções cognitivas e funcionalidade motora em idosos com doença de Alzheimer
Keywords: Alzheimer's disease; apathy; cognition; motor activity; doença de Alzheimer; apatia; cognição; atividade motora